Cyclin-Dependent Kinase-Like 5 (CDKL5): Possible Cellular Signalling Targets and Involvement in CDKL5 Deficiency Disorder - Katayama, Syouichi (Neural Plast, 2020)
Cyclin-dependent kinase-like 5 (CDKL5, also known as STK9) is a serine/threonine protein kinase originally identified in 1998 during a transcriptional mapping project of the human X chromosome. Thereafter, a mutation in CDKL5 was reported in individuals with the atypical Rett syndrome, a neurodevelopmental disorder, suggesting that CDKL5 plays an important regulatory role in neuronal function. The disease associated with CDKL5 mutation has recently been recognised as CDKL5 deficiency disorder (CDD) and has been distinguished from the Rett syndrome owing to its symptomatic manifestation. Because CDKL5 mutations identified in patients with CDD cause enzymatic loss of function, CDKL5 catalytic activity is likely strongly associated with the disease. Consequently, the exploration of CDKL5 substrate characteristics and regulatory mechanisms of its catalytic activity are important for identifying therapeutic target molecules and developing new treatment. In this review, we summarise recent findings on the phosphorylation of CDKL5 substrates and the mechanisms of CDKL5 phosphorylation and dephosphorylation. We also discuss the relationship between changes in the phosphorylation signalling pathways and the Cdkl5 knockout mouse phenotype and consider future prospects for the treatment of mental and neurological disease associated with CDKL5 mutations.